SEBUAH UPAYA PENINGKATAN PROFITABILITAS BERDASAR DANA PIHAK KETIGA MELALUI KONSEP PEMBIAYAAN SYARIAH: AN EFFORTS TO INCREASE PROFITABILITY BASED ON THIRD PARTY FUNDS THROUGH SHARIA FINANCING CONCEPT - Dimas Adi Wicaksono; Heru Yulianto; Mudjiyono Indonesia; Bambang Widjanarko Susilo (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2022)
The study aims to empirically test the influence of third-party funds in increasing profitability through Murabaha mediation. This basic model of research is expected to be able to contribute to science, to increase the profitability of Islamic banking. This research model was tested on six Islamic Banks registered with the Financial Services Authority (OJK) in 2015-2020 which are samples of the population. Determination of data is done using the purposive sampling method, with the path analysis approach technique through SPSS software. The results of this study show that there is no influence of DPK on Murabahah financing or Profitability, so Murabahah financing is not able to act as a mediation variable, on the other hand Murabahah financing has an influence on Profitability.